The Impact of Digitalisation of Social Media on Muslim Fashion Marketing: A Case Study of Al-Fath Muslim Fashion Store in Surakarta - Nugraha, Bima Wahyu Adi (Universitas Muhammadiyah Surakarta, 2023)
The increasing prevalence of smartphones has led to a shift in consumer behaviour towards accessing and purchasing goods through mobile devices. This trend has extended to marketing and distribution of products, including at Al-Fath Muslim Fashion Store in Surakarta. The purpose of this research is to investigate the impact of social media digitalisation on product marketing. This study uses a qualitative research method and employs data collection techniques such as observation and interviews with Al-Fath Muslim Fashion Store employees and consumers in Surakarta. The findings suggest that the implementation of social media digitalization by Al-Fath Surakarta has a significant impact on the marketing of their products. Social media serves as a promotional and product launching tool, providing widespread access and visibility of Al-Fath Surakarta's products. Furthermore, the store appeals to customers beyond the Surakarta area, and social media assists these customers in locating their desired products.